Perbandingan Aplikasi Konsep Simbiotik Kisho Kurokawa dengan Biomimetik Arsitektur pada Kebun Raya Mangrove Surabaya - Rumaseb, Fioletta Agustine; Zakariya, Afif Fajar (Universitas Medan Area, 2025)
Mangrove forests are the key to maintaining coastal ecosystems. However, mangrove forests in Indonesia itself have been reduced due to the reasonable transfer of land from tree felling due to infrastructure development. Meanwhile, a conservation architectural design approach that focuses on creating a balanced and mutualistic relationship in buildings with nature and surrounding living things has not yet been developed. Kisho Kurokawa's symbiotic theory and the concept of architectural biomimetics have similar principles in creating a beneficial relationship between humans and nature, aiming to preserve nature in architectural design. The aim of this study is to develop an architectural approach by comparing the principles of symbiosis and biomimetic for mangrove conservation design. The research method starts from studying and comparing the principles of symbiotic and biomimetic design, then the data results are examined whether they have been applied in the Surabaya Mangrove Botanical Garden. This comparison resulted in six a mangrove conservation design strategy, there are aspects of natural forms, connecting humans with nature, raising traditional aspects of the environment, natural materials, adapting to the environment, and maintaining sustainability. These six aspects improve traditional values ranging from social and cultural while maintaining the surrounding mangrove environment.